2003
DOI: 10.1021/jp034483f
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions of Malonic and Oxalic Acid Aerosols

Abstract: Atmospheric aerosol has been shown to contain an organic component that includes a significant fraction of small dicarboxylic acids, particularly in the urban environment. As an initial step toward understanding the phase in which particles may exist, a detailed study into the phase transitions of malonic and oxalic acid aerosols has been carried out. Both the aerosol phase transitions (deliquescence and efflorescence) and bulk solution properties (equilibrium water vapor pressure and the solubility and freezi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
164
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(189 citation statements)
references
References 25 publications
23
164
1
1
Order By: Relevance
“…However, formation of AN solids from the initially aqueous particles via heterogeneous nucleation in the presence of sulfate crystals was evident. Peng et al (2001) reported that MA particles did not crystallize at low RH of ∼5%, such crystallization events were observed by Braban et al (2003) at 6% RH. During the growth process, the abrupt increase in both the ν(C=O) peak's position and fwhh at 67% RH indicates deliquescence, consistent with Peng's bulk measurement of 65.3% RH and Braban's determination of 69% RH (Peng et al 2001;Braban et al 2003).…”
Section: Phase Transitions Of Single-component Systemsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, formation of AN solids from the initially aqueous particles via heterogeneous nucleation in the presence of sulfate crystals was evident. Peng et al (2001) reported that MA particles did not crystallize at low RH of ∼5%, such crystallization events were observed by Braban et al (2003) at 6% RH. During the growth process, the abrupt increase in both the ν(C=O) peak's position and fwhh at 67% RH indicates deliquescence, consistent with Peng's bulk measurement of 65.3% RH and Braban's determination of 69% RH (Peng et al 2001;Braban et al 2003).…”
Section: Phase Transitions Of Single-component Systemsmentioning
confidence: 96%
“…Peng et al (2001) reported that MA particles did not crystallize at low RH of ∼5%, such crystallization events were observed by Braban et al (2003) at 6% RH. During the growth process, the abrupt increase in both the ν(C=O) peak's position and fwhh at 67% RH indicates deliquescence, consistent with Peng's bulk measurement of 65.3% RH and Braban's determination of 69% RH (Peng et al 2001;Braban et al 2003). For GA, the CRH has been reported as 29-33% (Peng et al 2001) and 22.5-36% (Pant et al 2004).…”
Section: Phase Transitions Of Single-component Systemsmentioning
confidence: 96%
“…Several recent studies have addressed the hygroscopic behaviour (deliquescence and efflorescence phase transitions) and ice nucleation abilities of low molecular weight dicarboxylic acids (Braban et al, 2003;Kanji et al, 2008;Mikhailov et al, 2009;Parsons et al, 2004;Prenni et al, 2001;Shilling et al, 2006;Treuel et al, 2008;Zobrist et al, 2006). These compounds have been identified as an important contribution to the water-soluble organic fraction of the tropospheric aerosol, typically comprising 1-3% of the total particulate organic carbon in urban and semiurban areas and up to 10% in remote continental and marinecases, oxalic acid (C2) is found to be the most abundant species, followed by malonic (C3) and succinic acid (C4).…”
Section: Introductionmentioning
confidence: 99%
“…In the following, we will give a brief literature survey on the hygroscopic properties of oxalic acid, starting with the aerosol flow tube/FTIR study by Braban et al (2003). The authors have generated a polydisperse aerosol of anhydrous oxalic acid particles by spray-drying of an aqueous solution at a relative humidity (RH) of less than 5%.…”
Section: Introductionmentioning
confidence: 99%
“…Several initial studies have focused on the properties of water-soluble organic compounds (WSOC) that are found in the atmosphere. Dicarboxylic acids, which have been identified globally in atmospheric aerosol (Narukawa et al, 1999;Rohrl and Lammel, 2001;Yao et al, 2002;Narukawa et al, 2002), have been considered by several recent phase transition studies (Prenni et al, 2001;Brooks et al, 2002;Braban et al, 2003;Marcolli et al, 2004;Parsons et al, 2004;).…”
Section: Introductionmentioning
confidence: 99%